Expanded newborn screening for inherited metabolic disorders by tandem mass spectrometry in a northern Chinese population - Zhang, Hong; Wang, Yanyun; Qiu, Yali; Zhang, Chao (Frontiers in Genetics, 2022)
Tandem mass spectrometry (MS/MS) has been developed as one of the most important diagnostic platforms for the early detection and screening of inherited metabolic disorders (IMDs). To determine the disease spectrum and genetic characteristics of IMDs in Suqian city of Jiangsu province in the northern Chinese population, dried blood spots from 204,604 newborns, were assessed for IMDs by MS/MS from January 2016 to November 2020. Suspected positive patients were diagnosed through next-generation sequencing (NGS) and validated by Sanger sequencing. One hundred patients with IMDs were diagnosed, resulting in an overall incidence of 1/2,046, of which 56 (1/3,653), 22 (1/9,300), 22 (1/9,300) were confirmed amino acids disorders (AAs), organic acids disorders (OAs), fatty acid oxidation disorders (FAODs) positive cases, respectively. The highest incidence of IMDs is phenylalanine hydroxylase deficiency (PAHD) (45 cases), with a total incidence of 1:4,546. Hot spot mutations in phenylalanine hydroxylase (PAH)-related genes are c.158G>A (24.44%), c.728G>A (16.67%), c.611A>G (7.78%), and c.331C>T (7.78%). The related hot spot mutation of the MMACHC gene is c.609G>A (45.45%). Short-chain acyl-CoA dehydrogenase deficiency (SCAD)-related ACADS gene hotspot mutations are c.164C>T (33.33%) and c.1031A>G (33.33%). Our work indicated that the overall incidence of IMDs is high, and the mutations in PAH, ACADS, and MMACHC genes are the leading causes of IMDs in Suqian city. The incidence of AAs in Suqian city is higher than in other Chinese areas. The disease spectrum and genetic backgrounds were elucidated, contributing to the treatment and prenatal genetic counseling of these disorders in this region.